Aspergilloma of the Lung: Strategy to Prevent Endobronchial Spillage. Issue 5 (September 2016) - Roy, Preety Mittal; Khanna, Sangeeta; Mehta, Yatin; Khan, Ali Zamir
Aspergilloma of the lung eroding into the airway may lead to perioperative endobronchial spillage and contamination of the normal lung. Our aim in this group of patients who are undergoing robotic- or video-assisted thoracoscopic lobectomy is to protect the contralateral lung and, if possible, uninvolved lobes of ipsilateral lung. Doublelumen endobronchial tubes do provide lung protection to the contralateral lung intraoperatively, but there is no protection to the ipsilateral lung lobes not involved by the disease process. Moreover, there is no lung protection against endobronchial spillage during the period of induction of general anesthesia, when the cough reflex and gag reflex are absent. We have devised a technique to advance from side selection to lobe selection, that is, selective lobar isolation to prevent perioperative contamination of uninvolved lung lobes. This technique has two components viz positioning of the patient and securing the airway. The technique can also be used in other conditions such as hydatid cyst of the lung, lung abscess communicating with the airway and bleeding into the airway.